2021
DOI: 10.1186/s12884-021-03651-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the National Health Insurance Scheme helping pregnant women in accessing health services? Analysis of the 2014 Ghana demographic and Health survey

Abstract: Background Increasing the use of healthcare is a significant step in improving health outcomes in both the short and long term. However, the degree of the relationship between utilization of health services and health outcomes is affected by the quality of the services rendered, the timeliness of treatment and follow-up care. In this study, we investigated whether the National Health Insurance Scheme (NHIS) is helping pregnant women in accessing health services in Ghana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
(31 reference statements)
1
16
0
Order By: Relevance
“…The overall findings showed positive results where the beneficiaries had over 50 percent access to key healthcare services at health facilities at the local level in Ghana. This finding concurs with some recent studies on pregnant women' increased access to maternal healthcare services under NHIS in Ghana (Ameyaw et al, 2021;Ekholuenetale and Barrow, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall findings showed positive results where the beneficiaries had over 50 percent access to key healthcare services at health facilities at the local level in Ghana. This finding concurs with some recent studies on pregnant women' increased access to maternal healthcare services under NHIS in Ghana (Ameyaw et al, 2021;Ekholuenetale and Barrow, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the free maternal health policy has a positive effect on NHIS enrolment (Agbanyo, 2020;Okoroh et al, 2020;Umar et al, 2020;Ekholuenetale and Barrow, 2021). Despite this positive aspect of NHIS, other studies identified some challenges including distance travel to accredited health facilities, travel cost and perceived poor quality of healthcare services rendered to NHIS beneficiaries (Kodom et al, 2019;Ameyaw et al, 2021).…”
Section: Literature Review Implementation Of the Nhis And Implementers And Beneficiaries' Perspectives On Qualitymentioning
confidence: 99%
“…We found that women with health insurance coverage were less likely to have prolonged length of hospitalization after vagina delivery. This is positive, as access to the national health insurance scheme (NHIS) eliminates some of the financial barriers that prevent pregnant women with low socioeconomic status from accessing healthcare services including antenatal care [26,27]. Ameyaw et al noted that over 78% of pregnant women admitted to the significance of the NHIS to healthcare accessibility in Ghana [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is positive, as access to the national health insurance scheme (NHIS) eliminates some of the financial barriers that prevent pregnant women with low socioeconomic status from accessing healthcare services including antenatal care [26,27]. Ameyaw et al noted that over 78% of pregnant women admitted to the significance of the NHIS to healthcare accessibility in Ghana [26]. Regardless, since the NHIS do not absorb all maternal health service-related cost [27], some women are detained after delivery due to their inability to afford payments [28].…”
Section: Discussionmentioning
confidence: 99%
“…Insurance Scheme. NHIS coverage has increased healthcare utilization among older adults [39] and improved access to maternal and child health services, including antenatal care [40,41] despite the challenges with inequalities. Individuals enrolled in the insurance scheme are reported to be significantly more likely to obtain prescriptions, visit clinics, and seek formal healthcare when sick [42].…”
Section: Acceptability Of Health Services Under the National Healthmentioning
confidence: 99%